KATUPAT KANDANGAN KULINER TRADISIONAL KAB HULU SUNGAI SELATAN - Maimunah (Institut Agama Islam Darul Ulum Kandangan, 2020)
: Katupat Kandangan is a culinary delicacy in Hulu Sungai Selatan Regency which has distinctive characteristics comperad to ketupat culinary in other regions in Indonesia. This study uses qualitative research methods, this methods used to examine natural objective conditions. The results found that katupat Kandangan is a culinary delicacy that has its own characteristics, both from the raw material and the manufacturing process, this is because all the ingredients are local products in Hulu Sungai Selatan Regency.